Vad innebär Cochlea implantat (CI) som rehabilitativt hjälpmedel för vuxna med postlingual dövhet? - Hallberg, Lillemor R-M; Ringdahl, Anders (Socialmedicinsk tidskrift, 2007)
Cochlea implantat (CI) ordineras numera allt oftare som rehabilitativt hjälpmedel till personer med allt bättre ”resthörsel” och omkring 40 nya operationer genomförs för närvarande per år på Hörselvårdsavdelningen, SUS i Göteborg. För att förstå vad det innebär för patienter med grav hörselnedsättning/vuxendövhet att leva med CI och hur deras livskvalitet påverkas, krävs både traditionellt kvantitativa studier på slumpmässigt utvalda grupper ur populationen och mer inträngande kvalitativa studier på strategiskt utvalda grupper. Två av våra studier, en med kvalitativ och en med kvantitativ ansats, kommer kortfattat att beskrivas i denna artikel och belyser hur metodologisk mångfald bidrar till önskvärd kunskapstillväxt på ett komplicerat område. Since about 20 years cochlear implants have been available as audiological aids for adults with postlingual deafness, i.e. profound hearing impairment or deafness acquired after development of a spoken language. The studies that will be briefly presented in the present paper aim at gaining a deeper understanding of what a cochlear implant (CI) means to adults with postlingual deafness and how quality of life is affected by the CI. We also intend to identify factors that can predict psychological well-being (quality of life). In a qualitative study it was found that the meaning attributed to having a CI referred to psychological and existential dimensions rather than to audiological factors, only. Having a CI as a rehabilitative aid means according to the informants coming back to life. In a quantitative study it was found that environmental factors, such as availability of social support, attitudes from others and chronological age explained about half of the variance in psychological well-being/quality of life. In line with Malterud (2001) we argue that medical research needs methodological multiplicity. Despite that qualitative and quantitative research differ concerning ontological and epistemological starting-points, methodologically the approaches should be seen as complementary rather than as incompatible. Keywords: cochlear implant; grounded theory; environmental factors; postlingual deafness